Pelatihan Dan Pendampingan Tata Cara Penghitungan Waris Bagi Santri Pondok Pesantren Al Urwatul Wutsqo Jombang - Qurrotul Ainiyah; Beny Sintasari; Ahmad Budiyono; Arif Rahman Hakim (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2023)
Pondok Pesantren Al Urwatul Wutsqo Jombang is an Islamic educational institution that has an important role in shaping the character and understanding of religion among the citizens. One of the crucial aspects of Islamic religion is the law of inheritance, which regulates the division of property after a person dies. A proper understanding of the system of inheritance counting is crucial to ensuring justice and harmony in society. This study is a community dedication aimed at improving the understanding of the methods of counting inheritance among the centers of Pondok Pesantren Al Urwatul Wutsqo Jombang. The approach involved theoretical training and practical support, as well as close collaboration with the hostel manager. This training covers a basic understanding of faraidh, the principles of inheritance counting in Islam, and their practical application. The results of the study showed a significant improvement in the central understanding of the methodology of inheritance counting. Santri not only understands the basic principles of inheritance law but is also able to apply them in real-life situations. Besides, the program also empowers centers to be agents of change in their communities. The program has planned advanced activities to maintain a sustainable understanding of the hereditary calculation scheme among the centurions. Although there are some obstacles during implementation, such as a tight timetable, steps will be taken to address these challenges in the future. The dedication of this community was successful in improving the understanding of the methods of counting inheritance among the centers of the Pondok Pesantren Al Urwatul Wutsqo Jombang. It shows the importance of inclusive and interactive religious education in shaping individual character and instilling the values of justice in society.